2022
DOI: 10.1017/s1431927622000824
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Mechanisms in Secondary Electron e-Beam-Induced Current (SEEBIC) Imaging

Abstract: Over the last few years, a new mode for imaging in the scanning transmission electron microscope (STEM) has gained attention as it permits the direct visualization of sample conductivity and electrical connectivity. When the electron beam (e-beam) is focused on the sample in the STEM, secondary electrons (SEs) are generated. If the sample is conductive and electrically connected to an amplifier, the SE current can be measured as a function of the e-beam position. This scenario is similar to the better-known sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…(f–h) Adapted by permission from John Wiley and Sons: Small Methods (ref ( 31 )), copyright 2022. (j–l) Adapted from Oxford University Press: Microscopy and Microanalysis ref ( 34 ), copyright 2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(f–h) Adapted by permission from John Wiley and Sons: Small Methods (ref ( 31 )), copyright 2022. (j–l) Adapted from Oxford University Press: Microscopy and Microanalysis ref ( 34 ), copyright 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Voltage applied to the device before acquiring image (c,d,e,f,g) was 3.3, 4, 4.6, 4.8, and 4.9 V, respectively. (g) Adapted from Oxford University Press: Microscopy and Microanalysis ref ( 34 ), copyright 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the use of MEMS devices with electron-transparent Si 3 N 4 windows and lithographically patterned electrodes to perform SEEBIC experiments. 34,44,45 It was demonstrated that the Si 3 N 4 membrane yields sufficient conductivity for the required charge transport. 34 Alternatively, conventional TEM grids can also be used for SEEBIC experiments.…”
Section: Experimenal Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated the use of MEMS devices with electron-transparent Si 3 N 4 windows and lithographically patterned electrodes to perform SEEBIC experiments. ,, It was demonstrated that the Si 3 N 4 membrane yields sufficient conductivity for the required charge transport . Alternatively, conventional TEM grids can also be used for SEEBIC experiments. , We used herein a sample carrier based on a 0.6-mm thick FR4 printed circuit board, designed to fit in a DENS Solutions Wildfire heating holder, which allows the use of a conventional copper TEM grid as a sample support …”
Section: Experimenal Methodsmentioning
confidence: 99%
“…Later, it was demonstrated that lattice-resolution imaging is feasible, as well as resistive contrast imaging, allowing visualization of resistive grain boundaries in multilayer ceramic BaTiO 3 capacitors . A series of papers by Dyck et al have been issued, focusing on charge carrier transport in graphene nanodevices and the use of SEEBIC for device failure analysis. SEEBIC allowed a clear distinction between single and multilayer graphene and visualization of cracks in graphene sheets.…”
mentioning
confidence: 99%